RESULTS OF ІNSPECTІON OF SOME PERSPECTІVE ІNTRODUCED SPECІES AT THE STATE ENTERPRІSE “KHARKІV FOREST RESEARCH STATІON” - Musienko S. І.; Lunachevskiy, L. S.; Lukyanets, V. A. (Forestry and Forest Melioration, 2018)
In Danilovskiy arboretum, which covers an area of 16 hectares, 222 species, 16 forms and 31 hybrid forms of trees and shrubs are accounted, which belong to 84 genera of 32 families. Pinus and Quercus are the most widely represented families. The Pіnus family is represented by 12 species, 17 interspecific hybrids and many forms. The Quercus family is represented by 12 species and 5 interspecific hybrids. Arboretum is located in Pivdenne forestry of the State Enterprise “Kharkiv Forest Research Station” of Ukrainian Research Institute of Forestry & Forest Melioration named after G.M. Vysotsky (URIFFM). Inspection of stands have been carried out for altitude-ecological cultures of Picea pungens and Juniperus virginiana, research cultures of Quercus rubra, Quercus hartwissiana, Picea pungens, Picea engelmannii, ?bies concolor, Pinus ponderosa. The results of the research are presented. Conclusions about acclimatization of these species and feasibility of their applying for forestry and horticulture are made.